PRIORITIZATION OF ROAD NETWORK CONSTRUCTION IN BACAN ISLAND OF NORTH MALUKU PROVINCE - Ludfi Djakfar; Mashudman Mashudman; Hendi Bowoputro (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
Bacan Island, located in South Halmahera, North Maluku Province, is a potential region with a variety of important sectors, such as plantations, fisheries, mining, tourism, industry and trade. Until recently, this potential has not been exploited fully due to lack of transportation infrastructure systems. The government has prepared the plan to construct the road network systems, which consist of five road segments connecting the potential regions. With limited funding available, it would be impossible to build the road in the same time. Therefore, an optimum and carefully planned prioritization program should be applied. The purpose of this study was to determine the priority of road construction on the island of Bacan using Important Performance Analysis and Analytical Hierarchy Process methods. The result shows that the criteria considered important in determining the prioritization of road construction are as follows: (a) accessibility, (b) linkage, (c) land use, (d) cost, (e) technical aspects, (f) economic, and (g) environment. It is recommended that the construction phases of the road network in Bacan Island are Labuha-Babang, Babang-Songa, Songa-Wayaua, Labuha-Sawadai, Sawadai-Kubung, Babang-Yaba, Labuha-Belang-belang, Belang-belang-Yaba, Songa-Wayatim, and Wayatim-Wayaua, consecutively.Keywords: road construction, Importance Performance Analysis , Analytical Hierarchy Process